Uso de gráficos de controle para o monitoramento contínuo da razão água-óleo em campos da Bacia Potiguar - Assunção, Carla Simone de Lima Teixeira (2018)
Currently, oil is the energy source most used in the world, however, the greatest application is produced by produced water (PA). This water doesn´t have a commercial price and treatment is necessary for disposable or for reinraft, during the recovery methods. In this way, the water produced management is costly and, therefore, it needs tools that support it. In addition, the water production levels proportion in relation to oil production levels is a variable that supports the field economic viability analysis. So, the present work proposes a methodology for continuous monitoring of the water-oil ratio based on control charts. However, the water-oil ratio data are autocorrelated, which generates needs to fit a model that minimizes this correlation for the application of these charts. In this way, the data were adjusted according to ARIMA models and the control charts were elaborated based on the resulting residues. The control graphs studied were Shewhart's charts and CUSUM. After this application, a simulation was performed to evaluate the performance of each of the graphs to determine the best monitoring method.